2015
DOI: 10.1016/j.jcmg.2015.04.016
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the Radiation Effects of Cardiac CT Angiography Using Protein and Genetic Biomarkers

Abstract: Objectives To evaluate whether radiation exposure from cardiac computed tomographic angiography is associated with DNA damage and whether damage leads to programmed cell death and activation of genes involved in apoptosis and DNA repair. Background Exposure to radiation from medical imaging has become a public health concern, but whether it causes significant cell damage remains unclear. Methods We conducted a prospective cohort study in 67 patients undergoing cardiac computed tomographic angiography (CTA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…27 Emerging data suggest, however, that there is variability in tissue response to radiation, the safe threshold may vary between individuals, and the risk relationship is not linear. 14,28 The present study aimed to (1) study the biological effect of radiation exposure in operators by measuring pATM and γ-H2AX expression in circulating lymphocytes after EVAR, (2) examine individual operator sensitivity to radiation exposure using γ-H2AX levels as a biomarker, and (3) evaluate the protective effect of wearing lower leg lead shielding.…”
mentioning
confidence: 99%
“…27 Emerging data suggest, however, that there is variability in tissue response to radiation, the safe threshold may vary between individuals, and the risk relationship is not linear. 14,28 The present study aimed to (1) study the biological effect of radiation exposure in operators by measuring pATM and γ-H2AX expression in circulating lymphocytes after EVAR, (2) examine individual operator sensitivity to radiation exposure using γ-H2AX levels as a biomarker, and (3) evaluate the protective effect of wearing lower leg lead shielding.…”
mentioning
confidence: 99%
“…An obvious but often overlooked drawback of microCT is the use of X-ray sources and the potential tissue damage caused by the ionizing radiation (Han & Yu, 2009;Daly, 2012). Although this has been considered a minor issue because of short scan times, some studies on animal organisms indicated irreversible cellular damage even by exposure to very low X-ray doses (Rothkamm & L€ obrich, 2003;Nguyen et al, 2015). However, respective X-rays effects on plant samples have never been investigated in detail, although previous studies indicated damage of plant tissues after microCT scans.…”
Section: Introductionmentioning
confidence: 99%
“…However, no increase in cancer risk is present in atomic bomb survivors who received less than 5 mSv [4]. A recent paper evaluating the effects of radiation on protein and genetic biomarkers in patients undergoing cardiac computed tomography showed no abnormalities in patients who received less than 7.5 mSv [5]. These findings suggest that computed tomography for cardiac function as it can be practiced today poses no measureable radiation exposure risk.…”
mentioning
confidence: 97%